Improved Pre-attentive Processing With Occipital rTMS Treatment in Major Depressive Disorder Patients Revealed by MMN - Guan, Muzhen; Liu, Xufeng; Guo, Li; Zhang, Ruiguo; Tan, Qingrong; Wang, Huaihai; Wang, Huaning (Frontiers in Human Neuroscience, 2021)
Objectives: To investigate the improvement effect of occipital repetitive transcranial magnetic stimulation (rTMS) combined with Escitalopram Oxalate tablets on pre-attentive processing in patients with first-episode, medication-naive depression. Methods Patients who were hospitalized between January and December of 2019 were selected. They were randomly divided into real occipital rTMS stimulation group with 27 cases and sham stimulation group with 24 cases. Both groups took Escitalopram Oxalate tablets, and the average daily drug dose was 15.294 ± 5.041 mg. Hamilton Depression Rating Scale (HAMD) was used to assessthe symptoms of depression before and after treatment, and mismatch negativity (MMN) was used to assess the improvement of pre-attentive processing before and after treatment. Results After 20 days of treatment, the total score of HAMD (13.495±3.700) in both groups was significantly lower than that before treatment (21.910 ± 3.841, F (1, 49) = 46, 3.690, p < 0.001). After treatment, the latency of MMN in the real stimulation group (182.204 ± 31.878 ms) was significantly lower than that in the sham stimulation group (219.896 ± 42.634 ms, p < 0.001), and the amplitude of MMN in the real stimulation group (− 7.107 ± 3.374 ms) was significantly higher than that in the sham stimulation group (− 2.773 ± 3.7 32 ms, p < 0.001). Conclusion Occipital rTMS treatment can enhance the early therapeutic effect and effectively improve the pre-attentive processing of patients with depression, and provide a scientific basis for the new target of rTMS therapy in clinical patients with depression.